Sistem Pendidikan di Belanda - Nadiatulkhairiyah Nadiatulkhairiyah; Adinda Deswita Putri; Mislaini Mislaini (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The Dutch education system is renowned for its flexibility, inclusivity, and high quality. From primary to higher education, the system emphasizes competency development, personalized learning, and adaptation to the needs of the global labor market. Primary education equips students with foundational knowledge, while secondary education offers academic and vocational tracks tailored to students’ interests and abilities. Higher education, consisting of research universities and applied sciences universities, integrates theory and practice to produce globally competitive graduates. Nevertheless, challenges such as high living costs and disparities in educational access remain significant issues. Through technology-driven and innovative approaches, the Netherlands continues to strengthen its education system to meet modern demands.